Mechanisms of Immune Evasion and Immune Modulation by Lymphoma Cells - Menter, Thomas; Tzankov, Alexandar (Frontiers in Oncology, 2018)
Purpose: Targeting cancer cells by modulating the immune system has become an important new therapeutic option in many different malignancies. Inhibition of CTLA4/B7 and PD1/PDL1 signaling is now also being investigated and already successfully applied to various hematologic malignancies. Methods: A literature review of PubMed and results of our own studies were compiled in order to give a comprehensive overview on this topic. Results: We elucidate the pathophysiological role of immunosuppressive networks in lymphomas, ranging from changes in the cellular microenvironment composition to distinct signaling pathways such as PD1/PDL1 or CTLA4/B7/CD28. The prototypical example of a lymphoma manipulating and thereby silencing the immune system is Hodgkin lymphoma. Also other lymphomas, e.g. primary mediastinal B-cell lymphoma and some Epstein-Barr virus driven malignancies, use analogous survival strategies, while diffuse large B-cell lymphoma of the activated B-cell type and , to name a few, exert further immune escape strategies each. These insights have already led to new treatment opportunities and results of the most important clinical trials based on this concept are briefly summarized. Immune checkpoint inhibition might also have severe side effects; the mechanisms of the rather un(der)recognized hematological side effects of this treatment approach are discussed. Conclusions: Silencing the host’s immune system is an important feature of various lymphomas. Achieving a better understanding of distinct pathways of interactions between lymphomas and different immunological microenvironment compounds yields substantial potential for new treatment concepts.